THE ERGONOMIC GYMNASTIC ON BLOOD PRESSURE AMONG ELDERLY - Yurike Septianingrum; Moh Haris Susanto (Nurse and Health: Jurnal Keperawatan, 2020)
Background: Pre elderly and elderly experience uncontrolled hypertension due to disobedience to diet and not regularly taking medication (Padila, 2013). Uncontrolled hypertension can cause stroke, heart trouble, coronary heart disease and death (Laily, 2017). One of the non-pharmacological therapies to reduce blood pressure elderly with hypertension is ergonomic gymnastic (Wratsongko, 2010).Objectives: The purpose of this study was to analyze the effect of ergonomic gymnastic on blood pressure among elderly.Methods: This study was pre-experimental with one-group pre-posttest design approaches. Population in this study were all elderly in Suko Village who matched the inclusion and exclusion criteria as many as 25 people. The sample of this study were 23 respondents and were taken by simple random sampling technique. Respondents were given ergonomic exercises for twice a week with a duration of 30 minutes. Blood pressure measurement data were taken using a sphygmomanometer and a stethoscope. Wilcoxon sign rank test with significance value less than .05 were used to analyzed data.Results: The results of the study there were significant differences between before and after doing ergonomic gymnastic with p value = 0.00, meaning that there was an influence of ergonomic gymnastics on blood pressure among elderly in Suko Village.Conclusion: The Ergonomic gymnastic can reduce blood pressure among elderly in Suko Village. The role of nurses is needed as a provider of geriatric nursing care, especially in hypertension geriatric Keywords: Hypertension, Ergonomic Gymnastic, Elderly, Blood Pressure.